Penalties For Cancelling Locked Gold Purchase Orders In Online Trading - Muhamad Zuhaili bin Saiman; Abdul Azib bin Hussain (Usim Press, 2024)
Journal of Muamalat and Islamic Finance Research (JMIFR) Volume 20 No.2 Page (99-111)